42.4k views
3 votes
What is the product of these binomials (X-6)(x+2)=

2 Answers

3 votes

Answer:

x^2 - 4x - 12

Explanation:

(x-6) (x+2)

= (x + -6) (x + 2)

= (x) (x) + (x) (2) + (- 6) (x) + (-6) (2)

= x^2 + 2x - 6x - 12

= x^2 - 4x - 12

Hope this helps!

User Timepilot
by
4.9k points
4 votes

Answer:

x^2 - 4x - 12

Explanation:

(x-6)(x+2) = x(x+2) - 6(x+2) = x^2+2x-6x-12 = x^2 - 4x - 12

i hope it helps

User Razvan Zamfir
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.